EKOWISATA (ONE PRODUCT ONE VILLAGE) DI DESA KURAU BARAT KABUPATEN BANGKA TENGAH - Ari Agung Nugroho; Darman Saputra; Julia Julia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2016)
Students are young intellectuals who are legally still students in an educational institution.education institution. It is only natural that the role of students in society must be realized with a real application. So that can have an impact positive development in the field of human resources. Lecture Real Work Lecture XI, University of Bangka Belitung University in the thematic field organized in Kurau Barat Village village aims to build tourism potential. Strategies that are built together to increase tourism potentialThe strategies built together to increase tourism potential consisted of ecotourism seminars, socialization of innovative products and making handicraft products. The implementation method was carried out through socialization to the community and to surrounding schools and directly providing a direct approach to the community's home which was carried out from July 20 to August 24, 2016.August 2016. Students were divided into 2 groups according to the main program that had been planned, namely group 1 (One Product One Village) and group 2 (1 Tree 1 Tourist). These programs are expected to build an interesting and newest tourist attraction for the community. attractive and up-to-date tourist attraction for the the welfare of the surrounding community.